Social capital, knowledge acquisition, and knowledge exploitation in young technology‐based firms - Yli‐Renko, Helena; Autio, Erkko; Sapienza, Harry J. (Strategic Management Journal, 2001)
Abstract Employing a sample of 180 entrepreneurial high‐technology ventures based in the United Kingdom, we examine the effects of social capital in key customer relationships on knowledge acquisition and knowledge exploitation. Building on the relational view and on social capital and knowledge‐based theories, we propose that social capital facilitates external knowledge acquisition in key customer relationships and that such knowledge mediates the relationship between social capital and knowledge exploitation for competitive advantage. Our results indicate that the social interaction and network ties dimensions of social capital are indeed associated with greater knowledge acquisition, but that the relationship quality dimension is negatively associated with knowledge acquisition. Knowledge acquisition is, in turn, positively associated with knowledge exploitation for competitive advantage through new product development, technological distinctiveness, and sales cost efficiency. Further, our results provide evidence that knowledge acquisition plays a mediating role between social capital and knowledge exploitation. Copyright © 2001 John Wiley & Sons, Ltd.